Agripreneurship insights and lessons from Agrocenta (Ghana) - Ocansey, Michael (Technical Centre for Agricultural and Rural Cooperation, 2018)
Michael Ocansey, CEO of Agrocenta (Ghana) shares how his initiative is helping farmers by linking them to large companies that can buy all their products, thus eliminating the middleman and fetch higher prices for their produce.